More Arrows in the Ancient DNA Quiver: Use of Paleoepigenomes and Paleomicrobiomes to Investigate Animal Adaptation to Environment. (22nd October 2019) - Liu, Yichen; Weyrich, Laura S; Llamas, Bastien
Abstract: Whether and how epigenetic mechanisms and the microbiome play a role in mammalian adaptation raised considerable attention and controversy, mainly because they have the potential to add new insights into the Modern Synthesis. Recent attempts to reconcile neo-Darwinism and neo-Lamarckism in a unified theory of molecular evolution give epigenetic mechanisms and microbiome a prominent role. However, supporting empirical data are still largely missing. Because experimental studies using extant animals can hardly be done over evolutionary timescales, we propose that advances in ancient DNA techniques provide a valid alternative. In this piece, we evaluate 1) the possible roles of epigenomes and microbiomes in animal adaptation, 2) advances in the retrieval of paleoepigenome and paleomicrobiome data using ancient DNA techniques, and 3) the plasticity of either and interactions between the epigenome and the microbiome, while emphasizing that it is essential to take both into account, as well as the underlying genetic factors that may confound the findings. We propose that advanced ancient DNA techniques should be applied to a wide range of past animals, so novel dynamics in animal evolution and adaption can be revealed.